Determination of Trace Amounts of Benzalkonium Chloride by Liquid-Liquid Extraction-Spectrophotometry Method - Gh. Afshar, Z.; Parham, H. (Asian Journal of Chemistry, 2011)
This study describes a simple, sensitive and selective extraction-spectrophotometric method for the determination of trace amounts of cationic surfactant of benzalkonium chloride. The benzalkonium-orange II ion-pair in bufferic media is quantitatively extracted into chloroform and its absorbance is measured at 487 nm at room temperature. The effect of different variables such as solvent, volume of extracting solvent, volume of anionic reagent, pH, ionic strength (0.4 M NaCl) and shaking time is investigated and optimum conditions for quantitative extraction of benzalkonium is obtained. Linear calibration graph over the benzalkonium chloride concentration range 0.25-9.0 μg mL-1 and regression coefficient of 0.9999 is obtained. The relative standard deviation of ten replicate determinations of 5 μg mL-1 of benzalkonium chloride is 0.959 %. Limit of detection of the method is 0.054 μg mL-1. The interfering effect of 20 a large number of diverse ions on the determination benzalkonium chloride was studied. The method is used for determination of benzalkonium chloride in the washing solution vegetable and good results are obtained.